HUBUNGAN JENIS MONITOR DENGAN KELELAHAN MATA PADA KEGIATAN PRAKTIKUM DI LAB. KOMPUTER FST UIN SUNAN KALIJAGA - Muhammad Ikhwan Ardiansyah (Integrated Lab Journal, 2016)
This study examines the relationship type of monitor with eyestrain computer users in the computer lab of the Faculty of Science and Technology UIN Sunan Kalijaga. The study involved 192 respondents who use computers in the computer lab. Measurement of eyestrain performed by questionnaire to the respondent. The results showed that there has been eyestrain experienced by 160 respondents (83.3 %) . Pain in the neck, back and shoulders (13.7 %) is a sign of eyestrain often occur. Using chi square statistical test showed relationship between the type of monitor to eyestrain computer users (p-value = 0.043) . CRT monitor has a refresh rate that is smaller than the LCD monitor. The flicker on a CRT display make the eyes become tired quickly.